IMPACT OF BOTANICAL INSECTICIDES ON THE STINGLESS BEES, TETRAGONULA IRIDIPENNIS S. AND THE HONEY BEES, APIS MELLIFERA L. ADULTS BEES (HYMENOPTERA: APIDAE) - POOJA SINGH; M.S. KHAN; NEHA KUNJWAL (The Bioscan, 2015)
Among the six botanical insecticides (Garlic Oil, Zatropha Oil, Emamectin, NSKE, Azwain Oil and Neem Oil) tested forT. iridipennis, the peak mortality was obtained due to exposure of Garlic oil (90%) and Neem oil (90%) while NSKE (70%) showed least toxicity to bees after 3 days of exposure. In case of A. mellifera also, the Garlic oil (100%) and Neem oil (93.34%) were found to cause peak mortality but Zatropha oil (76.67%) proven least toxic to bees